Drag crisis of a circular cylinder near a plane boundary. (15th April 2018) - Yang, Fan; An, Hongwei; Cheng, Liang
Abstract: The pressure distribution and the hydrodynamic forces on a circular cylinder placed near a plane boundary are investigated experimentally over a range of Reynolds numbers ( Re ) of 1.1 × 10 5 –4.3 × 10 5 and gap ( G ) to cylinder diameter ( D ) ratio ( G / D ) of 0–1.0. The objective of the study is to quantify the influence of G / D on the force coefficients when the boundary layer on the cylinder surface transits from laminar to turbulent. The hydrodynamic forces acting on the cylinder are obtained by integrating the measured pressure around the cylinder surface. A significant drag reduction from about 0.9 to 0.35 is observed for G / D ≥ 0.5 in the range of Re  = 1.9 × 10 5 –2.7 × 10 5 . At smaller G / D values of 0.25 and 0.1, the drag coefficient shows much less reduction than those observed at larger G / D values. No obvious drag reduction is found at G / D  = 0.01 and 0. Based on the observed features of pressure distributions and force coefficients, the boundary layer transition from laminar to turbulent is inferred for all the gap ratios ( G / D = 0 ∼ ∞). Highlights: For G/D > 0.5, drag crisis happens inthe range of =1.9×10 5 ~ 2.7 ×10 5 . CD reduces toabout 0.35 after the drag crisis. Drag crisis exists at G/D = 0.25, andhappens at lower Re due to the high turbulence intensity close to the plane. Re has less effect on CL than on CD . As G/D increases, CL reduces. The wall proximity delays the gap side separation on the cylinder surface due to the favourable pressure gradient. The Re values covered here are similar to fieldconditions and the results will influence engineering practices potential.